2001
DOI: 10.1021/bi015713o
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Analysis of the Potential Antimicrobial Target Aspartate Semialdehyde Dehydrogenase

Abstract: Aspartate-beta-semialdehyde dehydrogenase (ASADH) lies at the first branch point in the biosynthetic pathway through which bacteria, fungi, and the higher plants synthesize amino acids, including lysine and methionine and the cell wall component diaminopimelate from aspartate. Blocks in this biosynthetic pathway, which is absent in mammals, are lethal, and inhibitors of ASADH may therefore serve as useful antibacterial, fungicidal, or herbicidal agents. We have determined the structure of ASADH from Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
74
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 23 publications
5
74
0
Order By: Relevance
“…However, it is unlikely to be an ASA-DH because its active site lacks the Cys residue required for the catalysis by ASA-DH (19). Our enzymatic studies with purified TM1643 showed no ASA-DH activity in either the forward or the reverse reaction.…”
Section: Fig 2 Reaction Catalyzed By Amino Acid Dehydrogenasesmentioning
confidence: 59%
See 2 more Smart Citations
“…However, it is unlikely to be an ASA-DH because its active site lacks the Cys residue required for the catalysis by ASA-DH (19). Our enzymatic studies with purified TM1643 showed no ASA-DH activity in either the forward or the reverse reaction.…”
Section: Fig 2 Reaction Catalyzed By Amino Acid Dehydrogenasesmentioning
confidence: 59%
“…This residue is strictly conserved among all family members and may be located near the C4 position of the nicotinamide ring in the closed form of the enzyme. In support of this observation, the His-193 residue is structurally equivalent to the catalytic His residue in ASA-DH (19).…”
Section: Fig 2 Reaction Catalyzed By Amino Acid Dehydrogenasesmentioning
confidence: 67%
See 1 more Smart Citation
“…The structures of ASADHs from Escherichia coli (8,9) and from Vibrio cholerae (10) were recently solved, both as the apoenzyme and as a ternary complex with NADP and a covalently bound active site inhibitor, S-methyl-L-cysteine sulfoxide (SMCS). Each of these structures has further clarified the role of several active site amino acids identified earlier by site-directed mutagenesis (11).…”
mentioning
confidence: 99%
“…5A). Interdomain movement upon the binding of NADP ϩ was reported in aspartate-␤-semialdehyde dehydrogenases (28,29); however, this was not the case for TtLysY. A comparison of the present TtLysY structure with the apo-TtLysYHB8 structure revealed that both structures were essentially the same (root mean square deviation ϭ 0.4 Å).…”
Section: Ttlysy Catalyzes the Nadph-dependent Reduction Ofmentioning
confidence: 55%